2022
DOI: 10.3389/pore.2022.1610635
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological Implications of ASAP1 Expression in Hepatocellular Carcinoma

Abstract: Background: The expression of ArfGAP with SH3 domain ankyrin repeat and PH domain 1 (ASAP1) is increased in various types of cancer, showing potential as a prognostic marker. The clinicopathological implications of ASAP1 expression in patients with hepatocellular carcinoma (HCC) remain unclear. We thus investigated the clinicopathological significance and prognostic effect of ASAP1 expression in HCC patients.Materials and Methods: ASAP1 expression was assessed in 149 HCC tissue samples using immunohistochemist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…ASAP1 codes for ANK repeat and PH domain‐containing protein 1 (ASAP1), which plays a role in a number of different cellular functions, such as protein transportation, membrane trafficking, cell motility, and tumor invasion (Hou et al, 2014). There are several adverse health outcomes associated with increased ASAP1 expression, including melanoma, glioblastoma, hepatocellular carcinoma, ovarian cancer, and bladder cancer (Bang et al, 2022; Hou et al, 2014; Li et al, 2019; Wei et al, 2021; Yang et al, 2017). Additionally, elevated ASAP1 protein is found in metastatic prostate cancer cases (Lin et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…ASAP1 codes for ANK repeat and PH domain‐containing protein 1 (ASAP1), which plays a role in a number of different cellular functions, such as protein transportation, membrane trafficking, cell motility, and tumor invasion (Hou et al, 2014). There are several adverse health outcomes associated with increased ASAP1 expression, including melanoma, glioblastoma, hepatocellular carcinoma, ovarian cancer, and bladder cancer (Bang et al, 2022; Hou et al, 2014; Li et al, 2019; Wei et al, 2021; Yang et al, 2017). Additionally, elevated ASAP1 protein is found in metastatic prostate cancer cases (Lin et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Sato et al reported that high expression of ASAP1 protein in head and neck squamous cell carcinoma is associated with poor prognosis [ 12 ]. Bang et al reported that high ASAP1 expression is associated with poor prognosis in hepatocellular carcinoma [ 13 ]. Lou et al reported that higher expression of ASAP1 and FAK is associated with higher stage, poor differentiation, lymph node metastasis, and worse prognosis in the gastric cancer [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…ArfGAP with SH3 domain, ankyrin repeat, and PH domain 1 (ASAP1) protein modulates various functions in cells such as receptor recycling, vesicle formation, and cell motility by interacting with a diverse range of proteins in the ADP-ribosylation factor (ARF) family [ 8 ]. Previous studies have reported that the increased expression of ASAP1 promotes invasiveness and metastasis in cancer [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. The majority of these studies also have reported that the increased expression of ASAP1 is associated with poor prognosis in various types of cancer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation